Comparison of reticulocyte parameters between male rowers and non-rowers - Deng, X. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Introduction: The aim of this paper is to describe the characteristics of reticulocyte parameters within a group of male rowers.